External mass transfer model for the hydrolysis of palm olein using immobilized lipase - Chew, Yin Hoon (Institution of Chemical Engineers, 2008)
The application of immobilized enzyme in packed-bed reactor is gaining interest in the industry as it offers advantages over conventional chemical reactions. However, external mass transfer limitation is significant in immobilized enzyme packed-bed reactors, especially at large scales. This study aimed to develop an external mass transfer model for immobilized lipase (EC 3.1.1.3) during the hydrolysis of palm olein. A mass transfer correlation model of the form JD = KRenâˆ’1 was developed based on the literatures. The Colburn factor, JD, which is a function of Reynolds and Schmidt numbers, can be related to the external mass transfer coefficient, km. The values of K and n were determined by conducting experimental work at different mass flow rates. It was found that the values of K and n are 0.093 and 0.5, respectively. Since the average mass transfer coefficients can be correlated in terms of dimensionless groups which characterize the flow conditions, this model can be used for reactor scale-up design.